2016
DOI: 10.1038/tp.2016.130
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in emotional processing as a marker of clinical response to SSRI treatment in depression

Abstract: Antidepressant treatment reduces behavioural and neural markers of negative emotional bias early in treatment and has been proposed as a mechanism of antidepressant drug action. Here, we provide a critical test of this hypothesis by assessing whether neural markers of early emotional processing changes predict later clinical response in depression. Thirty-five unmedicated patients with major depression took the selective serotonin re-uptake inhibitor (SSRI), escitalopram (10 mg), over 6 weeks, and were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 32 publications
(50 reference statements)
9
106
1
Order By: Relevance
“…Elevated pretreatment anterior cingulate activity is most often reported in resting state or facial emotion tasks [6]. Furthermore, the time points of measurement might impact results, since early response might underlie a different neuronal activity as late response [42,43]. A sigmoid response indicates that individual patients respond with a moderate decline of HAM-D values in the beginning, followed by at a certain period of faster response and an again flatter decline at the end of observations.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated pretreatment anterior cingulate activity is most often reported in resting state or facial emotion tasks [6]. Furthermore, the time points of measurement might impact results, since early response might underlie a different neuronal activity as late response [42,43]. A sigmoid response indicates that individual patients respond with a moderate decline of HAM-D values in the beginning, followed by at a certain period of faster response and an again flatter decline at the end of observations.…”
Section: Discussionmentioning
confidence: 99%
“…We believe our findings provide support for: 1) the theory that an acute enhancement of GABAergic activity is a common mechanistic pathway across diverse antidepressant agents; and 2) further investigation of acute increases in glutamine/glutamate ratios and GABA levels in pgACC as potential early biomarkers of response to SSRI treatment in MDD. Overall, this study adds to the existing functional neuroimaging literature (Di Simplicio et al, 2012; Godlewska et al, 2016; Harmer et al, 2009) demonstrating changes in the brain early in antidepressant treatment that may mediate later clinical response – findings that may ultimately be valuable in developing novel depression treatments and informing clinical decision-making.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent study, Godlewska and colleagues 62 found that clinical response to escitalopram after 6 weeks of treatment was associated with early change during affective processing in the amygdala, thalamus, cingulate, and insula. The responder group showed a greater reduction in neural response in these areas during the processing of negative versus positive facial expressions, consistent with the hypothesis that these early changes are important for the expression of later clinical benefit.…”
Section: Explaining the Delayed Clinical Onset Of Antidepressant Drugsmentioning
confidence: 99%
“…In line with this hypothesis, early change in the perception and neural response to positive facial expressions has been associated with subsequent improvement in depression severity. 50,51,62 A classification-based approach of data from Tranter and colleagues' study 50 suggests that if an early change in positive processing is not seen with antidepressant treatment, patients have little chance of responding to this same treatment later (table 1). A similar effect was seen in older adults in which a group of patients with depression who did not show an improvement in the recognition of happy faces after 1 week of citalopram treatment also did not respond after 8 weeks of treatment.…”
Section: Explaining the Delayed Clinical Onset Of Antidepressant Drugsmentioning
confidence: 99%